(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2023)
Among the occupations, medical practitioners are thought to be the most sensitive. Because they are in direct contact with people and their life. As a result, these two parties communicate using the channel of speech. At this time, we thought it was appropriate to define terms like "speech culture" and "speech etiquette."